2012
DOI: 10.1371/journal.pone.0050837
|View full text |Cite
|
Sign up to set email alerts
|

MiR-101 and miR-144 Regulate the Expression of the CFTR Chloride Channel in the Lung

Abstract: The Cystic Fibrosis Transmembrane conductance Regulator (CFTR) is a chloride channel that plays a critical role in the lung by maintaining fluid homeostasis. Absence or malfunction of CFTR leads to Cystic Fibrosis, a disease characterized by chronic infection and inflammation. We recently reported that air pollutants such as cigarette smoke and cadmium negatively regulate the expression of CFTR by affecting several steps in the biogenesis of CFTR protein. MicroRNAs (miRNAs) have recently received a great deal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
106
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 136 publications
(113 citation statements)
references
References 28 publications
7
106
0
Order By: Relevance
“…For example, the orthologous hsa-miR-200c-3p that was enriched in the rat lung tissues and upregulated upon nitrofen treatment exhibited seed conservation with its host gene. Our findings, with regard to lung development, are consistent with increasing evidence from human studies on the effects of teratogenic and toxic triggers on miRNA profiling, and reconcile with orthologous studies matching the nitrofen-mediated upregulation of rat miR-101a-5p, -3p and human miR-144-5p in vivo in human airway epithelial cells upon cigarette smoke (16). Both of these miRNAs are also known to target genes associated with lung diseases such as the cystic fibrosis transmembrane conductor regulator gene in human (16).…”
Section: Rat Mirnas and Their Target Mrnas Could Function Similarly Tsupporting
confidence: 89%
“…For example, the orthologous hsa-miR-200c-3p that was enriched in the rat lung tissues and upregulated upon nitrofen treatment exhibited seed conservation with its host gene. Our findings, with regard to lung development, are consistent with increasing evidence from human studies on the effects of teratogenic and toxic triggers on miRNA profiling, and reconcile with orthologous studies matching the nitrofen-mediated upregulation of rat miR-101a-5p, -3p and human miR-144-5p in vivo in human airway epithelial cells upon cigarette smoke (16). Both of these miRNAs are also known to target genes associated with lung diseases such as the cystic fibrosis transmembrane conductor regulator gene in human (16).…”
Section: Rat Mirnas and Their Target Mrnas Could Function Similarly Tsupporting
confidence: 89%
“…The data confirms previous studies implicating miR-145 and miR-101 as important modulators of CFTR expression [5,6,8,9] and build on them by demonstrating how MBBOs based on these miRNAs can affect CFTR gene expression and CFTR protein function. The authors suggest that the MBBOs may be developed as tools for CFTR correction in people with CF.…”
supporting
confidence: 89%
“…Although multiple studies exist regarding the regulation of ion channels by miRNAs, [30][31][32] our results demonstrate that miR-21/PTEN/AKT pathway involves LXA 4 and LPS regulation of ENaC-γ protein expression. However, there are three aspects that need to be further addressed.…”
Section: Discussionmentioning
confidence: 58%
“…27 Recent studies revealed that miR-21 was dynamically regulated in LPS-induced ALI. 28,29 Also, studies have showed that miR-16 upregulated ENaC-β, 30 miR-101 and miR-144 targeted cystic fibrosis transmembrane conductance regulator 3′ UTR, 31 miR-96 and miR-330 bound to the 3' UTR of aquaporin 5. 32 Previous studies demonstrated that each specialized pro-resolving mediator regulated a distinct panel of miRNAs.…”
mentioning
confidence: 99%